Up from the ashes : rebuilding Japan after World War II - Ohlenroth, Pat. (Detroit : Lucent Books, 2008)
Explains cultural, political, and social developments in post-World War II Japan.
The long 1950s -- Double-digit growth: the 1960s -- Shocked! the 1970s -- Japan, Inc.: the 1980s -- The lost decade -- Japan in the twenty-first century.
Includes bibliographical references (p. 87-96) and index.
Keywords: Japan -- History -- 1945- -- Juvenile literature; Japan -- History -- 1945-